Cancer and fertility preservation: international recommendations from an expert meeting. Issue 1 (December 2016) - Lambertini, Matteo; Del Mastro, Lucia; Pescio, Maria; Andersen, Claus; Azim, Hatem; Peccatori, Fedro; Costa, Mauro; Revelli, Alberto; Salvagno, Francesca; Gennari, Alessandra; Ubaldi, Filippo; La Sala, Giovanni; et al.
Abstract In the last years, thanks to the improvement in the prognosis of cancer patients, a growing attention has been given to the fertility issues. International guidelines on fertility preservation in cancer patients recommend that physicians discuss, as early as possible, with all patients of reproductive age their risk of infertility from the disease and/or treatment and their interest in having children after cancer, and help with informed fertility preservation decisions. As recommended by the American Society of Clinical Oncology and the European Society for Medical Oncology, sperm cryopreservation and embryo/oocyte cryopreservation are standard strategies for fertility preservations in male and female patients, respectively; other strategies (e.g. pharmacological protection of the gonads and gonadal tissue cryopreservation) are considered experimental techniques. However, since then, new data have become available, and several issues in this field are still controversial and should be addressed by both patients and their treating physicians. In April 2015, physicians with expertise in the field of fertility preservation in cancer patients from several European countries were invited in Genova (Italy) to participate in a workshop on the topic of "cancer and fertility preservation". A total of ten controversial issues were discussed at the conference. Experts were asked to present an up-to-date review of the literature published on these topics and the presentation of own unpublished data was encouraged. On the basis of the data presented, as well as the expertise of the invited speakers, a total of ten recommendations were discussed and prepared with the aim to help physicians in counseling their young patients interested in fertility preservation. Although there is a great interest in this field, due to the lack of large prospective cohort studies and randomized trials on these topics, the level of evidence is not higher than 3 for most of the recommendations highlighting the need of further research efforts in many areas of this field. The participation to the ongoing registries and prospective studies is crucial to acquire more robust information in order to provide evidence-based recommendations.